Maternal protein restriction during pregnancy affects gene expression and immunolocalization of intestinal nutrient transporters in rats - Pinheiro, Daniela F. [UNESP]; Pinheiro, Patricia F.F. [UNESP]; Buratini, José [UNESP]; Castilho, Anthony C.S. [UNESP]; Lima, Paula F. [UNESP]; Trinca, Luiza A. [UNESP]; Vicentini-Paulino, Maria de Lourdes M. [UNESP] (Portland Press, 2013)
Intrauterine dietary restriction may cause changes in the functioning of offspring organs and systems later in life, an effect known as fetal programming. The present study evaluated mRNA abundance and immunolocalization of nutrient transporters as well as enterocytes proliferation in the proximal, median and distal segments of small intestine of rats born to protein-restricted dams. Pregnant rats were fed hypoproteic (6% protein) or control (17% protein) diets, and offspring rats were evaluated at 3 and 16 weeks of age. The presence of SGLT1 (sodium-glucose co-transporter 1), GLUT2 (glucose transporter 2), PEPT1 (peptide transporter 1) and the intestinal proliferation were evaluated by immunohistochemical techniques and the abundance of specific mRNA for SGLT1, GLUT2 and PEPT1 was assessed by the real-time PCR technique. Rats born to protein-restricted dams showed higher cell proliferation in all intestinal segments and higher gene expression of SGLT1 and PEPT1 in the duodenum. Moreover, in adult animals born to protein-restricted dams the immunoreactivity of SGLT1, GLUT2 and PEPT1in the duodenum was more intense than in control rats. Taken together, the results indicate that changes in the small intestine observed in adulthood can be programmed during the gestation. In addition, they show that this response is caused by both up-regulation in transporter gene expression, a specific adaptation mechanism, and intestinal proliferation, an unspecific adaptation mechanism.
Keywords: Fetal programming; Intestinal transporter; Peptide transporter 1 (PEPT1); Sodium-glucose co-transporter 1 (SGLT1); glucose transporter 2; messenger RNA; peptide transporter 1; sodium glucose cotransporter 2; adult animal; animal tissue; cell proliferation; controlled study; duodenum; female; gene expression; immunolocalization; immunoreactivity; intestine cell; male; maternal nutrition; nonhuman; priority journal; progeny; protein restriction; rat; real time polymerase chain reaction; small intestine; Adaptation, Physiological; Adiposity; Animal Nutritional Physiological Phenomena; Animals; Body Weight; Cell Proliferation; Diet, Protein-Restricted; Disease Models, Animal; Female; Gene Expression Regulation; Glucose Transporter Type 2; Immunohistochemistry; Intestine, Small; Malnutrition; Maternal Nutritional Physiological Phenomena; Membrane Transport Proteins; Pregnancy; Rats; Rats, Wistar; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Sodium-Glucose Transporter 1; Symporters